GAMBARAN EMOSI MAHASISWA DALAM MERESPON PENGINTEGRASIAN QUIZIZZ DI KELAS AKUNTANSI - David Firna Setiawan; Ika Indriasari (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
The positive impact of integrating educational applications on emotions is not clearly illustrated. Empirical facts only provide a few indications that the integration of educational applications has a positive impact on participation, attention and motivation. Even though these indicators are closely related to students' emotions. Through the integration of Quizizz in learning, this study aims to describe students' emotions in responding to the integration of Quizizz in accounting class. The research was conducted on students in the first semester of the management study program who are registered and taking online lectures in cost accounting courses. The research method used was an experiment using the one-shot case study model. The results showed that students' emotions in responding to the integration of quizzes in the accounting class were described proportionally including positive and negative emotions. Emotional changes occur in three stages, namely, (1) panic, (2) pleasure and (3) boredom. Keywords: Accounting Class, Emotion, Quiziz